Case Report: Long-Term Response to Radiotherapy Combined With Targeted Therapy in Histiocytic Sarcoma Harboring Mutations in MAPK and PI3K/AKT Pathways - Liu, Zijian; Xiao, Yin; Liu, Xinxiu; Li, Qiuhui; Liu, Tao; Zhu, Fang; Wu, Gang; Zhang, Liling (Frontiers in Oncology, 2021)
Background: Histiocytic sarcoma (HS) is a rare hematopoietic malignancy with an aggressive clinical presentation associated with a poor overall survival. To date, surgical resection, radiation therapy and chemotherapy were often utilized for HS, but curative effects are rather disappointing. Case presentation: A 19-year-old female was referred to our hospital with a pathologic diagnosis of HS in December 2017. The patient had a severe airway obstruction resulting from a large mass (6.0 cm×4.4 cm) arising from the left parapharyngeal space. She did not respond to CHOEP (cyclophosphamide, doxorubicin, vincristine, prednisone, and etoposide) chemotherapy, then she was switched to radiotherapy and crizotinib according to next-generation sequencing (NGS) results (mutations in MET and MAP2K1). The patient got a partial response after radiotherapy and crizotinib, then she switched to imatinib combined with thalidomide treatment. The patient got a long-term complete response from the treatment, and is alive 44 months after initial diagnosis without disease-progression. Further KEGG pathway enrichment analysis of NGS results from patient’s tissue revealed that phosphatidylinositol 3′ kinase (PI3K)/AKT and mitogen-activated protein kinase (MAPK) pathways were activated in this HS patient. We further performed experiments in vitro in a canine histiocytic sarcoma cell line DH82, in order to explore the possible mechanism of imatinib plus thalidomide in HS. Results of cell counting kit-8 (CCK8) assays showed that the proliferation activity of DH82 was significantly inhibited by imatinib but not thalidomide. Combined thalidomide with imatinib did not improve the inhibitory effects of imatinib to DH82. Results of western blot confirmed the inhibitory effects of imatinib on DH82 by targeting activation of MAPK and PI3K/AKT pathways. Conclusion: Radiotherapy combined with targeted therapy guided by NGS may be promising and further perspective clinical trial is warranted for the localized HS.